1997
DOI: 10.1042/cs0930195
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Measurement of Cardiac Output and Ventricular Ejection Fractions in Chronic Cardiac Failure: Relationship to Impaired Exercise Tolerance

Abstract: 1. The role of cardiac output limitation in the pathophysiology of exercise in patients with chronic failure remains undefined. During steady-state submaximal exercise, oxygen uptake is similar in patients and control subjects, but it is not known if cardiac output is also similar. We wished to determine if the reduced exercise tolerance of patients with chronic cardiac failure during such exercise is related to reduced cardiac output, or to peripheral factors. 2. Ten male patients with stable chronic failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…In contrast, in the present study population, there was no correlation between BNP and 6MWT at hospital discharge after admission for CHF. This finding is in contrast to two other outpatient studies [13,14]. The patients in these two studies, however, were in different stages of their disease, and not all of them were clinically stable.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In contrast, in the present study population, there was no correlation between BNP and 6MWT at hospital discharge after admission for CHF. This finding is in contrast to two other outpatient studies [13,14]. The patients in these two studies, however, were in different stages of their disease, and not all of them were clinically stable.…”
Section: Discussioncontrasting
confidence: 83%
“…Dracup et al also found no correlation between LVEF and 6MWT, which is generally considered a measure of submaximal exercise capacity [10]. Other investigators showed that exercise intolerance in CHF patients was more related to peripheral abnormalities than to central cardiac function [12,13]. Despite this, two recent relatively small studies, performed in an outpatient clinic setting, showed a significant and positive correlation between BNP and 6MWT in patients with CHF [14,15].…”
Section: Introductionmentioning
confidence: 94%
“…V9E at any given V9CO 2 is typically increased. Contributory factors include: premature metabolic acidaemia (reflecting reduced O 2 delivery and/or utilisation) [146,147]; increased physiological dead space [4]; increased sympathetic system activation via mechano-or pressor-receptor stimulation in the exercising muscles [148][149][150][151][152] and, possibly, contributions from cardiopulmonary vagal and sympathetic reflexes [132,153,154]. Several studies have shown that breathing pattern in CHF is more rapid and shallow than in healthy controls at any given V9E [4,155,156].…”
Section: Ventilatory Abnormalitiesmentioning
confidence: 99%
“…Previously, this impairment was ignored, and attention was paid to the relationships between the cardiac limitations and exercise capacity of the patients. However, numerous recent investigations have demonstrated that impairment of skeletal muscle function is also an important predictor of exercise limitation in CHF (Cotes, 1988) (Schols, 1991a) (Sullivan, 1995) (Steele, 1997). Regarding muscular involvement which coexists with cardiac impairment in CHF, there are numerous points in common with other chronic diseases (e.g., respiratory and collagen diseases).…”
Section: Bronchial Asthmamentioning
confidence: 99%